1990
DOI: 10.1111/j.1365-3016.1990.tb00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the relationship between a newborn assessment of gestational maturity and the gestational age interval

Abstract: This study examines the correlation and agreement between the calculated 'gestational interval' from the date of last menstrual period (LMP) and the Ballard newborn assessment of gestational maturity. It then investigates selected maternal socio-demographic, prenatal, intrapartum and infant factors which may account for differences between these two gestational age determination methods. Single live-born deliveries (n = 10,794) were selected from a 1982-1986 medical university perinatal information data system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…6,11 Some investigators, using physical and neurologic assessments, reported that Afro-American infants are more mature than white infants of the same GA. 13,14 In our study, the highest incidence of MSAF was found in black East Africans at all weeks of gestation compared with other ethnic groups, even after other independent variables such as GA, gravidity, and weight were controlled. (Figure 1).…”
Section: Discussionmentioning
confidence: 89%
“…6,11 Some investigators, using physical and neurologic assessments, reported that Afro-American infants are more mature than white infants of the same GA. 13,14 In our study, the highest incidence of MSAF was found in black East Africans at all weeks of gestation compared with other ethnic groups, even after other independent variables such as GA, gravidity, and weight were controlled. (Figure 1).…”
Section: Discussionmentioning
confidence: 89%
“…16 The association between the age at onset of feedings and the age at onset of NEC has been reported by others. [8][9][10]14 We observed in our EP infants with NEC that feedings were initiated at a mean of 4 days of age, and the mean age of onset of NEC was 20 days (range, 0-45 days). Our inverse correlation between GA and age of onset of NEC can be explained by the practice of more gradual advancement of enteral feeds in less mature infants who achieve sustained and full enteral nutrition at a later age compared to more mature infants.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon GA, all NEC infants were divided into the following five groups: extremely premature (EP, 23 to 26 weeks), very premature (VP, 27 to 29 weeks), moderately premature (MP, 30 to 34 weeks), near-term (NT, 35 to 36 weeks), and term (T, 37 to 42 weeks) groups. Gestational age was determined by a combination of prenatal ultrasound findings, maternal dates 10 and physical examination 11 by the attending neonatologist and was categorized by completed weeks of gestation. At the onset of signs or symptoms of NEC, serum electrolytes, a complete blood count, blood culture and arterial blood gas were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that the Dubowitz and/or Ballard methods overestimated GA by 2 or more weeks in as many as 45% to 75% of preterm infants [Spinnato et al, 1984;Shukla et al, 1987;Sanders et al, 1991]. In comparison with GA confirmed by obstetric ultrasonography before 20 weeks' gestation; the Ballard both overestimates GA in preterm infants and underestimates GA in post-term infants [Alexander et al, 1990[Alexander et al, , 1992b.…”
Section: Combination Of Neurological and Physical Criteriamentioning
confidence: 93%
“…It is a mistake to view measures of fetal size, duration of gestation, and degree of fetal maturation as synonymous; researchers and clinicians must make careful distinctions when discussing these concepts [Alexander et al, 1990;DiPietro and Allen, 1991;Alexander and Allen, 1996;Allen et al, 1998]. It is maturity at birth that determines survival and vulnerability to perinatal and neonatal complications.…”
Section: Measuring Gestational Agementioning
confidence: 97%